(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to Designing a Sharia Banking Wholesale Banking Business Modeling Strategy in Indonesia based on the principle of Tawhidi String Relation (TSR), knowing the right solution in Designing a Sharia Banking Wholesale Banking Business Modeling Strategy in Indonesia based on the principle of Tawhidi String Relation (TSR), Knowing the Modeling Strategy of Sharia Banking Wholesale Banking Business in Indonesia based on the principle of Tawhidi String Relation (TSR). This study used the Delphi method to determine the research model, data obtained from respondents consisting of experts, practitioners, academics, and regulators in this study were selected using the purposive sampling method. then the model was tested using the Analytic Network Process through the Super Decision software, then the research continued with the SEM-PLS test through Smart-PLS software. Based on the formulation of the problem, test results and research objectives, the researcher generally concluded that in determining the wholesale banking business modelling strategy based on the principles of Tauhidi String Relation (TSR), Islamic Banking in Indonesia needs to pay attention to several things based on current conditions, the strengths for Islamic banking are the Customer and Finance aspects, the weaknesses are Finance and Infrastructure, Islamic banking opportunities exist in the finance aspect, and Islamic banking must be aware of threats coming from the customer and finance aspects. Prior to this study, there was no reference for Islamic banking in establishing a wholesale banking segment business model, so Islamic banking became less focused on establishing its business growth strategy. These findings are a solution for Islamic banks in running the wholesale banking segment business, so that currently the Management of Islamic banking has known several crucial factors as a shaper of the wholesale banking business model that can be applied to Islamic banking in Indonesia.